2008
DOI: 10.1016/j.molbiopara.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The major surface protease (MSP or GP63) in the intracellular amastigote stage of Leishmania chagasi

Abstract: The Leishmania spp. protozoa have an abundant surface metalloprotease called MSP (major surface protease), which in Leishmania chagasi is encoded by three distinct gene classes (MSPS, MSPL, MSPC). Although MSP has been characterized primarily in extracellular promastigotes, it also facilitates survival of intracellular amastigotes. Promastigotes express MSPS, MSPL, and two forms of MSPC RNAs, whereas amastigotes express only MSPL RNA and one MSPC transcript. We confirmed the presence of MSPC protein in both pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 64 publications
(85 reference statements)
2
55
0
2
Order By: Relevance
“…2D), we observed that L. donovani amastigotes did not induce Syt XI degradation (Fig. 2C) (18,56). Similarly, infection with promastigotes of the nonpathogenic L. tarentolae species did not lead to Syt XI degradation (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…2D), we observed that L. donovani amastigotes did not induce Syt XI degradation (Fig. 2C) (18,56). Similarly, infection with promastigotes of the nonpathogenic L. tarentolae species did not lead to Syt XI degradation (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…1D), implying that GP63-mediated downmodulation of Wnt5a protein level is a possibility during infection of macrophages by L. donovani promastigotes and amastigotes. Because of probable differences in the cellular distributions of GP63 in promastigotes versus amastigotes (32), the modes of GP63-mediated reduction of Wnt5a protein by L. donovani promastigotes and amastigotes may be different. Involvement of phenanthroline-inhibitable metalloproteases other than GP63 in the downmodulation of Wnt5a protein levels is also possible (33).…”
Section: Donovani Infection Leads To Disruption Of the Steady-statmentioning
confidence: 99%
“…Moreover, similar to fibronectin, coating polystyrene surfaces with GP63 enhances in vitro spreading of fibroblasts (42). The expression of specific gp63 genes in the intracellular amastigote form (27,43,44) implies an intra-host cell function for this parasitic protease. Interestingly, the activity of GP63 was implicated in the protection of encapsulated proteins against phagolysosomal degradation as well as intra-macrophage survival of Leishmania mexicana amazonensis (45,46).…”
mentioning
confidence: 99%